Development of Methods to Evaluate Several Levels of Uranium Concentrations in Drainage Water Using Total Reflection X-Ray Fluorescence Technique - Matsuyama, Tsugufumi; Izumoto, Yukie; Ishii, Kota; Sakai, Yasuhiro; Yoshii, Hiroshi (Frontiers in Chemistry, 2019)
As a country’s law stipulates the effluent standard uranium concentration in drainage water, the uranium concentration must be determined when drainage water is released from a uranium handling facility, such as the Fukushima Daiichi nuclear power plant. The maximum allowable limit for uranium release at each facility is defined taking into consideration the situation of the facility, such as 1/10 to 1/100 of this effluent standard value. Currently, the uranium concentration of drainage water is commonly determined by α-particle spectrometry, in which several liters of drainage water must be evaporated, requiring about half of a day followed by 2–3 h of measurements, due to the low specific radioactivity of uranium. This work proposes a new methodology for the rapid and simple measurement of several levels of uranium in drainage water by a total reflection X-ray fluorescence (TXRF) analysis. Using a portable device for TXRF measurements was found to enable measurements with 1/10 the sensitivity of the effluent standard value by 10 times condensation of the uranium-containing sample solution; a benchtop device is useful to measure uranium concentrations less than 1/100 of the effluent standard value. Therefore, the selective usage of methods by a portable and benchtop devices allows for screening and precise evaluation of uranium concentrations in drainage water.